A Natureza das causativas sintéticas com verbo transitivo no português brasileiro - Glenda Aparecida Queiroz Milanio (2019)
This thesis aims at investigating the behavior of causative sentences, specifically the synthetic causative formed with transitive verb (SCTV), in Brazilian Portuguese. We identified that sentences like Congresswoman cuts her hair and I operated this eye are examples of SCTV. These constructions have the causation expressed by means of a synthetic structure, at the morphophonological level. In the literature, this construction has been identified as resulting from a lexico-semantic alternation (CANÇADO, 2007[2010] and NEGRÃO, CANÇADO and LUNGUINHO, 2013). However, we have assumed that it is a derivation, in which the SCTV has, at an underlying level, a structure analogous to the analytic causative, presenting a paraphrase compatible with: "Congresswoman made someone cut her hair. In order to develop this research, we analyze the causative sentences, in a diachronic and synchronic perspective .For this, we compare data from modernPortuguese (18th century) to data from contemporary Portuguese (20th-21st centuries).The results pointed out that causative constructions are subject to a cyclical process of transformation, according to Fleischman (1982), in which there is a competition betweenanalytical and synthetic forms. In addition, based on the theory of grammaticalization (HOPPER and TRAUGOTT, 1993, and LEHMANN, 1988), we verified that the causatives are exposed to an intense syntactic dependency between the main clause and the embedded clause. We also observed a plasticity in the arrangement of the constituents of the causative. We assume that these factors culminated in the loss of the morphology of the main clause verb and in the non-realization of the subject of the clause embedded in the SCTV. In terms of syntactic behavior, based on Chomsky (1995), Pylkkänen (2002, 2008), and Blanco (2010, 2011), we verified that the causative constructions are structured around two functional head: VoiceP and vPCAUSE. We also observed, as specificities of the causative, that the subject of the embedded clause receives a Nominative Case, because it is in a flexed context (RAPOSO, 1987, VITRAL, 1987, GONÇALVES and DUARTE, 2001, and LIMASALLES and PILATI, 2014). Following Floripi and Nunes (2009), we verified that in the SCTV there is a zero possessive context, which explains the correference with the position of subject. Finally, based on Bruening (2013), we reformulated the representation of the underlying level of SCTV, assuming two structures. In the first structure, in the position of subject of the embedded clause, there is a pro, which is interpreted as an indeterminate subject. In the second structure, the PP caused agent, when carried out phonologically, will saturate the VoiceP projected below vPCAUSE.